An Analysis Of Descriptive Text Written By The 8th Grade Students Of Smp 1 Muhammadiyah Pati In 2015/2016 Academic Year. - Sofyan Susanto, Ali, Aryati Prasetyarini, S.Pd., M.Pd (2017)
This research aims to describe the students' capability in writing descriptive text, to identify the problem faced by the students in writing descriptive text and to identify the causes of the problem faced by the students in writing descriptive text at the 8th grade student of SMP 1 Muhammadiyah Pati in 2015/2016 academic year. The method of colecting data are observation,interview,analyzing document and test. The research analyzed the students' writing based on (a) Vocabulary, (b) grammar, (c) Organization of the paragraph, (d) Content of the composition (e) mechanic. After analyzing the texts written by the student, the researcher catagorizes them into four categories, namely excelent, good, fair,poor. The result is 1 student or 3,12%, there are 6 students or 18,75%, there are 3 students or 9,37%, there are 22 students or 68,75%. The average the students' capability in writing descriptive text is poor. The problems faced are (1) the students have problem with limited number of vocabulary, (2) developing the idea in a descriptive text, (3) grammar mastery. Grammar mastery is the most problem faced by the students. The causes of the problem are (1) students' low motivation, (2) Understanding.